2022
DOI: 10.4103/jfmpc.jfmpc_747_22
|View full text |Cite
|
Sign up to set email alerts
|

Ocular adverse effects of COVID-19 vaccines: A systematic review

Abstract: The COVID-19 pandemic has led to the development and rollout of several vaccines worldwide at unprecedented pace. This systematic review of published literature has been undertaken to spread awareness among general physicians and ophthalmologists about the various reported adverse effects in the eye following COVID-19 vaccination. A systematic search was performed on 25 January 2022 through PuBMed, Medline and Google scholar for publications on ocular adverse effects after COVID-19 vaccination. One brief commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…The most prevalent ocular complications reported in this study were classified as "ocular inflammatory complications", encompassing uveitis, anterior uveitis, posterior uveitis, scleritis, posterior scleritis, choroiditis, keratitis, acute retinal necrosis, and iridocyclitis, collectively accounting for 47.3% of all cases. These findings align with previous literature reviews [26,27], which identified uveitis as the most common ocular complication after receiving vaccines for various conditions. Notably, our study's predominant subtype of uveitis observed was anterior uveitis, representing 56% of cases.…”
Section: Discussionsupporting
confidence: 91%
“…The most prevalent ocular complications reported in this study were classified as "ocular inflammatory complications", encompassing uveitis, anterior uveitis, posterior uveitis, scleritis, posterior scleritis, choroiditis, keratitis, acute retinal necrosis, and iridocyclitis, collectively accounting for 47.3% of all cases. These findings align with previous literature reviews [26,27], which identified uveitis as the most common ocular complication after receiving vaccines for various conditions. Notably, our study's predominant subtype of uveitis observed was anterior uveitis, representing 56% of cases.…”
Section: Discussionsupporting
confidence: 91%
“…The rate of corneal allograft rejection secondary to COVID-19 vaccination is estimated at 0.004 per million, calculated by dividing the number of events by the number of doses (Moura-Coelho et al, 2023). Despite the inferred relation between the vaccine and rejection due to temporal association, within the systematic reviews which discussed corneal allograft rejection following COVID-19 vaccination, none found sufficient evidence to definitively conclude causation (Lee and Huang, 2021;Fujio et al, 2022;Huang et al, 2022;Kumari et al, 2022;Wang et al, 2022;Kuziez et al, 2023;Moura-Coelho et al, 2023). There is significantly more published literature on COVID-19 vaccination and corneal allograft rejection than any other type of vaccination, but the systematic reviews deduce this is likely confounded by the profound public interest in the COVID-19 vaccination, following the global pandemic, encouraging publication (Kuziez et al, 2023;Moura-Coelho et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…Ocular adverse events included eyelid edema and erythema; purpuric lesions on the eyelid; reactivation of herpes simplex keratitis; corneal epithelitis caused by the herpes zoster virus; acute graft rejection in repeat penetrating keratoplasty (PKP) cases; dual graft rejection in post-PK situations; acute endothelial rejection following Descemet’s Membrane Endothelial Keratoplasty (DMEK); reactivation of Vogt-Koyanagi-Harada disease (VKH); anterior and posterior uveitis; scleritis; bilateral choroiditis; toxoplasma retinochoroiditis; pars planitis; retinal vasculitis; bilateral panuveitis in cases of new-onset Behcet’s disease; multiple evanescent white dot syndrome (MEWDS); acute macular neuroretinopathy; retinal vein occlusions; non-arteritic ischemic optic neuropathy; activation of quiescent choroidal neovascularization (CNV) due to myopia or uveitis; central serous chorioretinopathy; bilateral acute anterior ischemic optic neuropathy (AAION); bilateral acute zonal occult outer retinopathy (AZOOR); PAMM, AMN; disc edema and central serous chorioretinopathy (CSCR); branch retinal arterial occlusion; combined arterial and venous occlusion; nerve fiber layer infarction; bilateral AMN; episcleritis; Bell’s palsy; abducens nerve palsy; optic neuritis; multiple cranial nerve palsies; Miller Fisher syndrome; bilateral superior ophthalmic vein thrombosis; immune thrombocytopenic purpura (ITP) and ischemic stroke; thyroid eye disease (TED); acute hemorrhagic conjunctivitis in systemic lupus erythematosus. 134–136 …”
Section: Ophthalmological Symptoms In the Course Of Covid-19mentioning
confidence: 99%